Reconstructing ontological foundations in islamic education management: a philosophical inquiry into being, leadership values, and institutional development - Hambali, Adang; Anshorudin , Rizal; Hidayat , Hidayat; Sidiq, Ade Abdullah; Salim , Agus (ARKA INSTITUTE, 2025)
Ontology constitutes the philosophical foundation for shaping knowledge systems and managerial paradigms within Islamic educational institutions. This study aims to reconstruct the ontological basis of Islamic education management through philosophical-conceptual inquiry, focusing on the nature of being, leadership identity, and institutional development anchored in Islamic metaphysics. Using a qualitative–philosophical approach through conceptual analysis and hermeneutic textual interpretation, this study examines how the Islamic worldview of al-wujūd informs leadership behavior, institutional identity, and organizational culture. The findings indicate that Islamic education management transcends technical administration, functioning instead as an ontological practice rooted in tawhid, human existence, and the civilizational mission of education. Grounded in classical scholarship (Al-Ghazali, Ibn Khaldun) and contemporary Islamic philosophers (Nasr), Islamic management emphasizes metaphysical consciousness, ethical leadership, and mission-driven institutional development. This study contributes to strengthening the philosophical architecture of Islamic educational leadership and highlights the urgency of ontological literacy for institutional transformation.